2021
DOI: 10.1002/1878-0261.13151
|View full text |Cite
|
Sign up to set email alerts
|

Pathway profiling of a novel SRC inhibitor, AZD0424, in combination with MEK inhibitors for cancer treatment

Abstract: A more comprehensive understanding of how cells respond to drug intervention, the likely immediate signalling responses and how resistance may develop within different microenvironments will help inform treatment regimes. The nonreceptor tyrosine kinase SRC regulates many cellular signalling processes, and pharmacological inhibition has long been a target of cancer drug discovery projects. Here, we describe the in vitro and in vivo characterisation of the small-molecule SRC inhibitor AZD0424. We show that AZD0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Some caution is suggested by the toxicity of the combination of saracatinib and vistusertib in our genetically-engineered mouse model. In future experiments, toxicity may be addressed through the dose of each compound, better scheduling or combination with new generation improved SRC inhibitors [99]. Nevertheless, our results show that saracatinib as single agent provides superior activity in this model than the current standard-of-care, extending the medium survival of asbestos-treated animals by 72 days without noticeable toxicity.…”
Section: Discussionmentioning
confidence: 78%
“…Some caution is suggested by the toxicity of the combination of saracatinib and vistusertib in our genetically-engineered mouse model. In future experiments, toxicity may be addressed through the dose of each compound, better scheduling or combination with new generation improved SRC inhibitors [99]. Nevertheless, our results show that saracatinib as single agent provides superior activity in this model than the current standard-of-care, extending the medium survival of asbestos-treated animals by 72 days without noticeable toxicity.…”
Section: Discussionmentioning
confidence: 78%
“…Among these combinations, we identified classes of PI3K/mTOR, SRC, and receptor tyrosine kinase inhibitors that are broadly synergistic with trametinib in KRAS-mutant cell lines. Importantly, some of these classes were previously identified as synergistic to MEK inhibitors and with our current knowledge of cell signaling pathways, these findings were anticipated; these findings increased our confidence that this method provides relevant information [ 42 45 ].…”
Section: Resultsmentioning
confidence: 85%
“…Researchers have examined the effects of the combination of SRC and MEK inhibitors on other cancer types with activation of the MAPK pathway [ 57 59 ]. Initial success of these studies provides a rationale for combining SRC inhibitors with MEK inhibitors in clinical studies [ 45 , 60 , 61 ]. This rationale is also supported by our in vitro studies that identifies dasatinib as a drug that enhances the efficacy of trametinib against KRAS-mutated CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from drugs directly targeting KRAS, a number of indirectly targeted therapies targeting its upstream or downstream signaling pathway have also been developed. A study found that AZD0424 (an SRC inhibitor), when combined with MEK inhibitors (such as trametinib), inhibits tumor growth more than MEK inhibitor monotherapy, but does not reverse pre-existing MEK inhibitor resistance [ 78 ]. A study of KRAS G12R-mutant pancreatic cancer patients treated with selumetinib (KOSELUGO™; ARRY-142886, an oral MEK1/2 inhibitor) showed a median PFS of 3.0 months and a median OS of 9 months.…”
Section: Therapeutic Strategies In Kras-mutant Cancersmentioning
confidence: 99%